Photo-generation profiles in deeply-etched, two-dimensional patterns in interdigitated back contact solar cells - Rais A.R.M.; Sepeai S.; Desa M.K.M.; Ibrahim M.A.; Ker P.J.; Zaidi S.H.; Sopian K. (S.C. Virtual Company of Phisics S.R.L, 2023)
Interdigitated back contact (IBC) crystalline silicon solar cell model has been developed by using SILVACO in order to achieve design optimization in non-conventional device configurations. The SILVACO software was employed to evaluate performance of IBC solar cell as a function of texture while keeping identical semiconductor process parameters including doping of emitter, BSF and FSF. Based on the period of the pyramidal texturing, the textured surface can be distributed uniformly throughout the solar cell as exhibited by the 40-?m period pattern for which the incident is uniformly and deeply penetrated inside the IBC solar cell. Therefore, efficiency of the IBC solar cell is boosted to 23.31% in comparison with 22.36% from planar IBC solar cell. The photo-generation profile for planar surface is not uniformly and deeply distributed throughout the IBC solar cell but for P40D20 the distribution of incident photons well distributed and penetrates deeper into IBC solar cell which leads to improved IBC solar cell performance. For IBC solar cells with periods larger than 40 ?m, performance is degraded due to formation of shadows within the solar cell located at grooves of pyramid. These shadows effectively reduce number of photons and therefore degrade solar cell performance. Hence, the texturization process can boost solar cell performance only if appropriate parameters are chosen otherwise reduced performance can result due to enhanced shadow effects inside the solar cell even though the front surface has no metallic contacts to physically block light. 2021, S.C. Virtual Company of Phisics S.R.L. All rights reserved.